2012
DOI: 10.1080/02640414.2012.692479
|View full text |Cite
|
Sign up to set email alerts
|

A faster running speed is associated with a greater body weight loss in 100-km ultra-marathoners

Abstract: In 219 recreational male runners, we investigated changes in body mass, total body water, haematocrit, plasma sodium concentration ([Na(+)]), and urine specific gravity as well as fluid intake during a 100-km ultra-marathon. The athletes lost 1.9 kg (s = 1.4) of body mass, equal to 2.5% (s = 1.8) of body mass (P < 0.001), 0.7 kg (s = 1.0) of predicted skeletal muscle mass (P < 0.001), 0.2 kg (s = 1.3) of predicted fat mass (P < 0.05), and 0.9 L (s = 1.6) of predicted total body water (P < 0.001). Haematocrit d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
50
1
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 40 publications
(58 citation statements)
references
References 63 publications
6
50
1
1
Order By: Relevance
“…Recently, Knechtle et al 22 found a mean reduction of 2.5% in the weight of athletes after a 100-km ultramarathon, which can not be totally explained by the reduction in total body water, suggesting that the loss resulted from solid mass loss (muscle mass and fat).…”
Section: Passaglia Et Al Effects Of Prolonged Physical Exercisementioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Knechtle et al 22 found a mean reduction of 2.5% in the weight of athletes after a 100-km ultramarathon, which can not be totally explained by the reduction in total body water, suggesting that the loss resulted from solid mass loss (muscle mass and fat).…”
Section: Passaglia Et Al Effects Of Prolonged Physical Exercisementioning
confidence: 99%
“…2013;100(1): [21][22][23][24][25][26][27][28] exercise at high temperatures 18 . It is noteworthy in our study the close inverse association observed between CPK levels and the covered distance.…”
Section: Passaglia Et Al Effects Of Prolonged Physical Exercisementioning
confidence: 99%
“…Therefore, athletes who drink less during ultra-marathon running may profit from body mass loss and complete the race faster [57]. Also in a 160-km ultra-marathon, greater loss in body mass during the race was not associated with impaired performance but was rather an aspect of superior performance [60].…”
Section: Fluid and Electrolyte Metabolism During Ultra-runningmentioning
confidence: 99%
“…In a 100-km ultra-marathon, faster runners drank more fluid than slower runners and faster runners lost more body mass than slower runners. Additionally, runners lost more body mass when they drank less fluid [57].…”
Section: Fluid and Electrolyte Metabolism During Ultra-runningmentioning
confidence: 99%
See 1 more Smart Citation